Condomínios residenciais fechados e as concepções de morar a partir das propagandas imobiliárias em São Luís - ALBUQUERQUE, Bruno Maia Correia de (2022)
Urban space, a place of human production, is also used by large construction companies as a political and strategic object. The city is the stage of a spatial segregation that marks the relationships between individuals. These differences are naturally presented by real estate advertisements as the great differential in choosing the dream property. Buying a house or an apartment is no longer just a necessity nowadays, but also an investment that is directly related to the neighborhood, the most varied services provided by the condominium and, most importantly, the type of person you will be when you experience it. that particular place. The work aims to make a comparative study of the real estate advertisements of two closed condominium developments and to reflect on taste and social distinction using the categories of cultural industry, economic field and habitus. Advertisements, tools of the Cultural Industry, by demarcating the tastes that will be shown to the public, build invisible differences between individuals who seek, in the differential, an element to be consumed.